TRANSFORMING MARKETING COMMUNICATIONS IN THE INDUSTRIAL SECTOR: CHALLENGES OF THE DIGITAL AGE - Blahun , I.I.; Shurpa , S.Y. (The actual problems of regional economy development, 2025)
The relevance of the study is driven by profound changes in the external environment of industrial enterprises, which are manifested in the rapid development of digital technologies, increased competition in global and local markets, a shift in the focus of consumer behaviour and the need to ensure transparent, effective and adaptive communication with various market participants. In the context of digital transformation, traditional marketing communication tools are losing their effectiveness, while new channels such as social media, mobile platforms, CRM systems, and automated analytics are becoming critical for building partnerships, increasing customer loyalty, and strengthening the brand. For Ukrainian industrial enterprises operating under martial law, disrupted supply chains, declining domestic demand and limited opportunities to enter foreign markets, digitalisation of communications is becoming strategically important. It allows them to increase competitiveness, ensure effective interaction with counterparties and respond quickly to changes in the market environment. The methodological basis of the study is based on systemic, comparative, structural and functional approaches, as well as analysis of modern theoretical sources and practical cases of industrial enterprises. As a result of the analysis, the main directions of digital transformation of marketing communications were identified: transition to integrated communication strategies, active use of digital marketing tools, in particular CRM systems, automated analytics, and personalised content. The scientific novelty of the study lies in systematising typical models of marketing communications transformation in the B2B segment and clarifying the role of digital innovations in the formation of new channels of interaction with partners and customers. The practical significance of the article lies in the possibility of using the results of the study to develop effective digital communications strategies at Ukrainian industrial enterprises that adapt to modern challenges, including post-war economic recovery and the growing digitalisation of production and sales.